2014
DOI: 10.3892/or.2014.3351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide synthase on multiple drug resistance is related to Wnt signaling in non-small cell lung cancer

Abstract: Multiple drug resistance (MDR) is considered a major challenge in the clinical treatment of non-small cell lung cancer (NSCLC). Both nitric oxide synthase (iNOS) and Wnt signaling pathway participate in the regulation of drug resistance, but the interaction between them remains unclear. In the present study, we detected the activation of Wnt/β-catenin signaling in iNOS-induced drug-resistant lung cancer cells, and compared the effect of canonical and noncanonical Wnt pathway on the level of iNOS. Moreover, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Wnt/β-catenin signaling pathway is also implicated in playing a critical role in EMT and appears to be associated with resistance to therapeutic treatment in aggressive types of cancer [16, 17, 2729]. Data from our previous study suggested that activation of Wnt3/β-catenin signaling pathway in HER2-overexpressing breast cancer cells leads to transactivation of EGFR and trastuzumab resistance [18].…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling pathway is also implicated in playing a critical role in EMT and appears to be associated with resistance to therapeutic treatment in aggressive types of cancer [16, 17, 2729]. Data from our previous study suggested that activation of Wnt3/β-catenin signaling pathway in HER2-overexpressing breast cancer cells leads to transactivation of EGFR and trastuzumab resistance [18].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, β-catenin accumulates in the nucleus, forming the β-catenin/TCF/LEF transcriptional complex, and drives transactivation of Wnt signaling–targeted genes which promote EMT [ 58 , 59 ]. Aberrations in the Wnt signaling pathway have been linked to many human cancers, including breast cancer, and appear to be associated with resistance to therapeutic treatment and aggressive types of cancer [ 60 , 61 , 62 ].…”
Section: Molecular Mechanisms Of Emtmentioning
confidence: 99%
“…[ 28 ] TOP2A induces drug resistance via Wnt signaling in NSCLC. [ 29 ] Biagioni et al (2012) showed that CCNA2 affects cell cycle regulation. [ 30 ] KIF20A overexpression confers a malignant phenotype to ovarian tumors by promoting proliferation and inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%